Identificação dos custos ambientais na unidade industrial de Passo Fundo-RS da Empresa Bünge Alimentos S.A. - Brandli, Elisangela Nicoloso (2008)
The environmental concern is increasing significantly last years and the companies need to adapt the environmental legislations that are more rigorous, for the conquest of new markets and also to satisfy the consumers needs, that are requiring environmentally correct products. In this context, the companies need to have more control about their environmental costs, identifying, classifying and measuring them, which will supply subsidies for the decisionmaking process. This research has as purpose the identification of the environmental costs of a food industry. For this end, was utilized the model proposed by Jasch (2001). It was utilized as theoretical base the sustainable development, echo-efficiency, environmental costs, and other ones. As regards the methodology was accomplished a case study, identifying the environmental costs involved in the productive process. The results of the research denoted that based on accountancy system utilized Currently the company was possible the identification of some the inherent environmental costs to the productive process, permitting a partial information of how much the company actually expenses with environment. Based in these results was proposed some procedures for the implementation of system of funding, the ABC, method and also for the implementation of the environmental costs identification model of Jasch, designing the company can account and present such costs. Through the implementation of the system of identification of environmental costs, the company may have more control over them, knowing how much spent on the environment. Knowledge of the costs related to the environment can lead to a reduction in the quantity of inputs used in operating activities and the reduction of pollutants emitted